1986
DOI: 10.1083/jcb.103.1.231
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular compartments in tendon morphogenesis: collagen fibril, bundle, and macroaggregate formation.

Abstract: Abstract. The formation of collagen fibrils, fibril bundies, and tissue-specific collagen macroaggregates by chick embryo tendon fibroblasts was studied using conventional and high voltage electron microscopy. During chick tendon morphogenesis, there are at least three extraceUular compartments responsible for three levels of matrix organization: collagen fibrils, bundles, and collagen macroaggregates. Our observations indicate that the initial extracellular events in collagen fibrillogenesis occur within narr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
241
0
2

Year Published

1988
1988
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 345 publications
(251 citation statements)
references
References 31 publications
8
241
0
2
Order By: Relevance
“…Electron microscopy (EM) has the resolution to study cellular interactions and has brought new understanding to the role of cells in the assembly of other matrix molecules, like collagen. EM studies have shown that collagen fibrillogenesis is initiated within plasma membrane recesses, presumably under close cellular regulation (Birk and Trelstad, 1986). Similar structures, given the name fibripositors, have been described in ligament cells (Canty et al, 2004).…”
Section: Cellular Activitymentioning
confidence: 79%
See 1 more Smart Citation
“…Electron microscopy (EM) has the resolution to study cellular interactions and has brought new understanding to the role of cells in the assembly of other matrix molecules, like collagen. EM studies have shown that collagen fibrillogenesis is initiated within plasma membrane recesses, presumably under close cellular regulation (Birk and Trelstad, 1986). Similar structures, given the name fibripositors, have been described in ligament cells (Canty et al, 2004).…”
Section: Cellular Activitymentioning
confidence: 79%
“…Cells are actively involved in assembling many ECM molecules, including fibronectin (Mao and Schwarzbauer, 2005) and collagen (Birk and Trelstad, 1986;Kadler, 2004), but their role in elastic fiber assembly has been overlooked. Recent live imaging studies in our laboratory show that cells are actively involved in the organization and alignment of elastin aggregates into linear structures and the deposition of elastin aggregates onto preexisting fibers Czirok et al, 2006).…”
Section: Cellular Activitymentioning
confidence: 99%
“…In situ data indicate that fibril segments are intermediates in collagen fibril assembly (Birk et al, 1989bBirk and Trelstad, 1986). Extraction of 14-day embryonic tendons yielded intact fibril segments.…”
Section: Discussionmentioning
confidence: 99%
“…Tissues were prepared for transmission electron microscopy essentially as described. 26,27 Briefly, tissues were fixed in 4% paraformaldehyde, 2.5% glutaraldehyde, 0.1 mol/L sodium cacodylate, pH 7.4, with 8.0 mmol/L CaCl 2 , postfixed with 1% osmium tetroxide. After dehydration in an ethanol series, followed by propylene oxide, the tissue samples were infiltrated and embedded in a mixture of Embed 812, nadic methyl anhydride, dodecenyl succinic anhydride, and DMP-30 (Electron Microscopy Sciences, Hatfield, PA).…”
Section: Transmission Electron Microscopymentioning
confidence: 99%